UPAYA MENUMBUHKAN JIWA KEWIRAUSAHAAN MELALUI PROGRAM RESELER TANPA MODAL DEMI MEMILIKI KEMANDIRIAN FINANSIAL PADA KOMUNITAS SEKMA CINANGSIH: Bahasa Indonesia - Arie Hendra Saputro; Andre Suryaningprang; Dadan Abdul Aziz Mubarok; Ridlwan Muttaqin; Rizki Surya Tawaqal (Universitas Mataram, 2023)
Financial independence is what the Cinangsih SEKMA Community desires. One way is to maximize the use of social media and e-commerce. Two weaknesses experienced by the Cinangsih SEKMA Community are that they do not have the desire to become entrepreneurs. The Cinangsih SEKMA community has not used social media and e-commerce well. One program that can be done is to take advantage of the reseller program without capital. Partners are still focused on socializing so they have not yet utilized it for entrepreneurship. This community service activity focuses on socialization and training for the Cinangsih SEKMA Community. Develop a desire for entrepreneurship and have the desire to utilize social media and e-commerce. This community service is carried out for 1 month for socialization, training and mentoring. Activities focus on socialization, fostering an entrepreneurial spirit and assistance in implementing reseller programs without capital. The solutions provided in this service program are 1) Socialization in fostering an entrepreneurial spirit, 2) Socialization in using social media and e-commerce, 3) Reseller Program without capital. The method used to overcome the problems faced by the Cinangsih SEKMA community is to explain, explain and assist in cultivating an entrepreneurial spirit. Another method is to utilize social media and e-commerce to implement it in a reseller program without capital. This community service is hoped by the SEKMA Cinangsih community to have financial independence by running a reseller program without capital. Cultivating an entrepreneurial spirit requires the role of a mentor who is ready to help and accompany. Financial independence requires the right method. One thing that can be utilized is by utilizing social media, applications and e-commerce.